Fulfillment of Human Rights to a Good and Healthy Environment in the Perspective of Spatial Planning in Pematangsiantar - Banjarnahor, Daulat Nathanael; Togatorop, Firinta (JURNAL SYNTAX IMPERATIF : Jurnal Ilmu Sosial dan Pendidikan, 2024)
Indonesia as a constitutional state, as well as a modern state, has a clear characteristic, namely that it clearly states the regulation of human rights in its constitution, the 1945 Constitution. Article 28H paragraph (1) of the 1945 Constitution states that "everyone has the right to a good and healthy environment". As a response to the needs and human rights for a good and healthy environment in the constitution, the Indonesian government established Law Number 26 of 2007 concerning Spatial Planning as a legal instrument for spatial planning throughout the territory of the Republic of Indonesia. One of the essential things regulated in this law can be seen in article 29 paragraph (3), namely the proportion of public green open spaces in a city area of at least 20 percent of the city area. The problems in this paper: first, how is the Effectiveness of the Fulfillment of Human Rights on a Good and Healthy Environment in the Spatial Planning Perspective in Pematangsiantar, and Second: the Factors Affecting the Effectiveness of the Fulfillment of Human Rights on a Good and Healthy Environment in the Perspective of Spatial Planning in Pematangsiantar. The research method used to answer the problems in this paper is the Normative Legal Research Method with a Literature Study-Based Conceptual Approach. The answer of paper problems is that the fulfillment of human rights for a good and healthy environment in the perspective of spatial planning in Pematangsiantar has not been effective with the influencing factors being the rule of law, apparatus, facilities, society, and culture. The conclusion drawn from the answers to this paper is that Fulfillment of human rights for a good and healthy environment in the perspective of spatial planning in Pematangsiantar has not been effective with several logical arguments. Factors Influencing the Effectiveness of the Fulfillment of Human Rights for a Good and Healthy Environment in the Perspective of Spatial Planning in Pematangsiantar can be seen from the aspects of the rule of law or legal substance, legal apparatus or legal structure, facilities, and legal culture or society.